2019
DOI: 10.1177/2045894019826944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hemodynamic benefit of macitentan and riociguat upfront combination in patients with pulmonary arterial hypertension

Abstract: In this open-label study, we evaluated the effect of upfront macitentan and riociguat combination in newly diagnosed pulmonary arterial hypertension (PAH) patients. In 15 consecutive PAH patients, we collected clinical and hemodynamic data at baseline, visit 1 (median 4 months) and visit 2 (median 12 months). Survival and transplantation status were analyzed over 36 months. Statistical analysis included student t-test and 95% confidence interval (CI) (t-statistic or Clopper-Pearson). Kaplan-Meier was used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…This exploratory analysis has allowed evaluation of patients who had only recently (within the previous three to six months) started ERA therapy before receiving riociguat, showing that early sequential combination therapy with an ERA plus riociguat was effective and well tolerated in this patient population. This is consistent with a recent report in which upfront combination therapy with riociguat and macitentan in patients with newly diagnosed PAH was associated with significant improvements in 6MWD, brain natriuretic peptide, and hemodynamic parameters 19 …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This exploratory analysis has allowed evaluation of patients who had only recently (within the previous three to six months) started ERA therapy before receiving riociguat, showing that early sequential combination therapy with an ERA plus riociguat was effective and well tolerated in this patient population. This is consistent with a recent report in which upfront combination therapy with riociguat and macitentan in patients with newly diagnosed PAH was associated with significant improvements in 6MWD, brain natriuretic peptide, and hemodynamic parameters 19 …”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a recent report in which upfront combination therapy with riociguat and macitentan in patients with newly diagnosed PAH was associated with significant improvements in 6MWD, brain natriuretic peptide, and hemodynamic parameters. 19 Limitations of the present analysis include its post hoc exploratory nature, and the limited patient numbers, particularly in the prostanoid group, with some outliers potentially biasing the data. There is no formal definition of ''early sequential'' combination therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] Other study demonstrated that riociguat obviously decreased mean pulmonary arterial pressure (47.3– 38.9 mmHg) and PVR (9.2– 5.7 wood units), and increased cardiac index. [ 25 ] Later, the study evaluated the effects of riociguat on hemodynamic parameters in Asian patients with inoperable CTEPH, and the results indicated that riociguat significantly reduced PAP (41– 38 mmHg) and PVR (787 to 478 dyn s cm −5 ), and relieved clinical symptoms. [ 26 ] These results were consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…There were no unexpected side effects, and the transplant-free survival rate was 85% at 36 months. 56…”
Section: Author Opinionmentioning
confidence: 99%